Ρυθμίσεις θεμάτων πετρέλευσης: βιβλιογραφική επισκόπηση - Κιουλαφλή, Βικτώρια (2020)
Since the first ships were created, the way of trading has changed worldwide.From the first wooden ships to the steamships of the 19th century, the people whose land was close to the sea, used the ships for commercial purposes, fishing, war, and even search for land. Today the shipping industry is active in various markets. Today's ships could not sail without fuel. That is the reason why the bunkering process and the choice of fuel for each ship is very important. As we move into the 21st century, the International Maritime Organization sets increasingly stringent regulations on emissions of pollutants and harmful substances into the environment. The use of alternative fuels is one solution to the problem. However, the International Maritime Organization sets an even stricter regulation for all ships. The "Sulphur Cap" regulation will be in operation since the beginning of 2020 and aims to reduce emissions of sulphur dioxide into the atmosphere.